The Effectiveness of Loan Provision and Education by Sawiran Cooperative to Farmers Regarding Crop Yields to Achieve More Profitable Harvests - Pamungkas, Prasetio Drajat; Fadil, Cholid (Unram Journal of Community Service, 2025)
The success of cooperatives in supporting farmers through capital loan programs and agricultural education depends on their ability to overcome key challenges, such as the dependence of farmers' income on the harvest season and the risk of crop failure due to extreme weather. To overcome this, the Sawiran cooperative developed an educational program that includes mulching drip irrigation techniques, allowing farmers to plant out-of-season and make optimal use of land. In addition, crop diversification is encouraged to increase farmers' income and reduce the risks resulting from dependence on one type of crop. Capital loans from cooperatives provide flexibility for farmers to manage farming finances, such as buying seeds, fertilizer or agricultural equipment. With initial capital, farmers can increase productivity and quality of harvest using modern technology introduced by cooperatives. In addition, the close relationship between cooperatives and farmers supports the financial stability of cooperatives and opens up opportunities for farmers to become permanent members. The benefits of this program include earlier harvests at higher selling prices, reduced risk of losses due to certain planting seasons, and diversification of farming businesses which increases farmers' economic resilience. However, the government's role is needed to complement cooperative efforts in providing comprehensive access to education and technology. It is hoped that good collaboration can create sustainable solutions to improve the welfare of farmers in the Ngadisari region